Pengembangan Zig-Zag Card Remind Sebagai Media Edukasi Gizi pada Penderita Hipertensi di Puskesmas Labruk Kidul Lumajang - Ayu Febriyatna; Putri Mardyana (Politeknik Negeri Jember, 2022)
One of the diseases that is currently a priority by the world of health globally or the world is hypertension. The prevalence of people experiencing hypertension in Labruk Kidul Health Center, Lumajang Regency is 43.91%. Hypertension sufferers cannot control their blood pressure because some hypertensive patients previously lacked education about hypertension. This is because the media which is only in the form of monotonous leaflets and no interesting poster media about hypertension, so it is not effective in overcoming the incidence of hypertension. Therefore, a research was conducted on the development of the Zig Zag Card Remind as a nutritional medium for hypertensive patients at Labruk Kidul Lumajang Health Center. This research method uses Research and Development (R&D) research using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The number of subjects in this study were 50 hypertensive patients at Labruk Kidul Health Center who were taken by accidental sampling. The results of research on the development of zigzag card remind media for hypertension sufferers from the feasibility test by material experts by 95% and 92% media experts, these results are a feasible category in field trials without revision then the media feasibility test results are 83.78%, meaning that that the product is very suitable for use as a media for nutrition education. It is recommended that this zig-zag card remind product be used as an educational medium for the benefit of further health research that involves educational intervention actions for other people.